Coronary cameral fistula to right atrium in a 10 year old male: a case report - Banday, M. Javed; Kumar, Sudesh; Bansal, Dhananjay; Bhusan, Rahul; Jhajhria, Narender Singh; Grover, Vijay; Gupta, Vijay Kumar (International Surgery Journal, 2019)
A coronary cameral fistula is a rare cardiac anomaly and involves an abnormal communication between one of the coronary arteries and a cardiac chamber. In most of cases, it is a congenital lesion and is asymptomatic in early life. Once symptoms appear, patient warrants early evaluation and treatment. Presently, CT Angiography is the best investigation for diagnosing the disease and the best treatment modality is surgical closure. We present a case of a 10 year old male with large coronary cameral fistula from right coronary artery to right atrium, who was symptomatic and was operated for the same.